Online studios and digital literacy skills among undergraduate students: An Activity Theory Perspective - Mhungu, Blessed (School of Education, 2025)
Recently, most higher education institutions have undergone significant technological transformation, largely attributed to the outbreak of COVID-19 pandemic and the subsequent rise in online education and the use of emerging technology tools . Consequently, the prevailing discourse no longer revolves solely around the feasibility of online education as a tool but pivots towards an inquiry into the extent of its usefulness in specialised domains such as design and technology fields. Research on the implementation of online education in design and technology fields is scant and yields inconclusive results, particularly concerning the pedagogical methods and the practicality of online instruction. As a result, investigating the practicality of online studios in enhancing digital literacy skills within the design and technology fields has , thus, become significant and urgent. Success in this endeavour hinges upon lecturers' proficiency with technological tools that facilitate cognitive development. This could necessitate the shift away from the traditional ‘master-apprentice' model to a more ‘cognitiveapprentice' model, which emphasises deeper understanding of the underlying principles, problemsolving techniques, and decision-making processes used by experts. The research question posed by the study was: What digital literacy skills do online studios promote among undergraduate students in a discipline-specific setting such design and information technology fields? The goal was to explore how educators in visual communication design programme and multimedia could transition from traditional studio methods to an online studio-based curriculum infused with technology. Theoretically, the study drew on Cultural Historical Activity theory (CHAT) sociocultural learning theory of Vygotsky, its influence on the three generations of activity that Engeström propounded, and the expansive learning model that Engeström developed. CHAT considered studio practices as a system of activities wherein collective work is undertaken by individual and group actors in pursuit of a common goal. Adopting an empirical exploratory case study approach, the study was conducted in a real-world context in real time, using multi-site, multi-method strategy for data collection and analysis. Data collection methods included interviews, focus groups and participant observations from students and lecturers at university of technology's faculty of Informatics and Design. The findings of this study reveal contradictions and tensions within the visual communication design programme and multimedia programme activity systems. Furthermore, the findings suggest that the transition to remote teaching during the COVID-19 pandemic presented an opportunity for lecturers to explore alternative methods to facilitate a studio pedagogy, most of which involve digital modalities of content delivery. The emergence of expansive learning fused with blended learning approach emerged as a ‘great-promise' for integrating technology into the studio. This approach is considered crucial in equipping students with relevant 21st century skills and enhancing their digital literacy, thereby addressing the evolving demands of design and technology education in the contemporary digital era.